Mucinous borderline tumor involving fallopian tube: case report and review of the literature - Liu, Fangfang (e-Century Publishing Corporation, 2013)
We report the case of a 74-year-old woman with a primary mucinous borderline tumor of the fallopian tube coexisting with an ovarian mucinous borderline tumor. Data were obtained through histopathologic study of the excised surgical specimen. p53, estrogen receptor (ER) and PAX8 expression were evaluated by immunohistochemistry on the available right fallopian tube and ovary. Both the ovarian and fallopian tube borderline ovarian tumors were negative for p53, ER and PAX8. However, the staining pattern highlighted the transition from a normal ciliated cell to neoplastic epithelia in the fallopian tube fimbria. This is the first report to indicate that mucinous borderline tumors may arise from the ciliated cells at the fallopian tube fimbrial epithelia. ER and PAX8 are useful markers in identifying the transition and origination of these tumors.